ANALISIS MANAJEMEN PENGUMPULAN (FUNDRAISING) ZAKAT PROFESI DI LAZ PERSADA PAMEKASAN DENGAN PRINSIP POAC - Rohman, Habibur (Investama : Jurnal Ekonomi dan Bisnis, 2025)
In the Islamic view, all aspects of human life are regulated in Islam, including economic aspects. Poverty has always been a never-ending problem. The instrument that can alleviate poverty in the Islamic view is known as zakat. LAZ PERSADA Pamekasan, which is one of the zakat amil institutions in Pamekasan, which is still relatively new, of course requires strategies and methods in conducting zakat fundraising so that people can channel their zakat to this institution. The aim of this research is to find out the mechanism or method of LAZ PERSADA Pamekasan in conducting zakat fundraising, as well as analyzing zakat fundraising in terms of the POAC aspect. This research uses descriptive qualitative research. Research findings at LAZ PERSADA in conducting zakat fundraising use two methods, namely direct fundraising and indirect fundraising, and at LAZ PERSADA Pamekasan they have implemented POAC well and effectively.